A tin-bismuth alloy material and a method for producing the same
By adding specific elements to Sn-Bi alloys and employing refined preparation methods, the brittleness and oxidation problems of Sn-Bi alloys have been solved, achieving stable use at high temperatures and excellent oxidation resistance and wetting properties.
Patent Information
- Application Number
- CN202410485439.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-04-22
AI Technical Summary
Sn-Bi alloys are brittle and have low ductility, resulting in poor machinability. They are also prone to oxidation at high temperatures and cannot completely replace lead solder.
Silver, wettability improver X, aluminum, nano-lanthanum oxide, germanium and cerium are added to Sn-Bi alloy. Through the synergistic effect of elements in a specific ratio, the brittleness, oxidation resistance and wettability of the alloy are improved. The preparation method adopts a stepwise heating, ultrasonic treatment and slow cooling method.
It improves the oxidation resistance, wettability and mechanical properties of tin-bismuth alloys, enhances the strength and plasticity of the alloys, and ensures stable use at high temperatures.
Smart Images

Figure BDA0004803580810000061
Abstract
Description
Technical Field
[0001] This application relates to the field of welding materials technology, and in particular to a tin-bismuth alloy material and its preparation method. Background Technology
[0002] The toxicity of lead has spurred research into novel lead-free solders, but to date, no alloy has been found that can completely replace tin-lead solder. Sn-Bi solder exhibits good thermal fatigue properties at room temperature, with better tensile strength and creep resistance than Sn-Pb solder. Furthermore, Sn-Bi solder can be alloyed within a melting temperature range of 138.8℃-232℃ without forming other Sn and Bi compounds. This is a characteristic not found in other solder alloy series. Due to the significant side effects of lead, research has focused on low-melting-point alloys to replace it, with considerable research concentrated on materials based on tin-bismuth alloys. Sn-Bi alloys possess good mechanical properties; at room temperature, they exhibit higher yield strength, shear strength, tensile strength, and creep resistance than SnPb solder, and also demonstrate good thermal fatigue properties. However, the inherent brittleness of Bi causes Sn-Bi alloys to exhibit high brittleness and low ductility, leading to reduced plasticity and, in severe cases, brittle fracture, which significantly affects machinability. Summary of the Invention
[0003] The purpose of this application is to address the shortcomings of current technologies by providing a tin-bismuth alloy material and its preparation method. The tin-bismuth alloy material of this application exhibits excellent oxidation resistance, wettability, and mechanical properties. By adding silver, wettability improver X, aluminum, nano-lanthanum oxide, germanium, and cerium to the Sn-Bi alloy, the coarsening and brittleness of Bi can be mitigated, thus improving the alloy properties. Appropriate amounts of aluminum and nano-lanthanum oxide can enhance the alloy strength of the tin-bismuth alloy, improve solder plasticity, and increase thermal fatigue strength and oxidation resistance. Germanium exhibits surface segregation characteristics, and high-temperature tin... After melting, it can precipitate onto the surface of the tin-bismuth alloy, preferentially combining with oxygen before elements such as tin, thus improving the surface oxidation resistance of the tin-bismuth alloy. At the same time, together with cerium, it can change the liquidus temperature of tin, enabling tin to work normally and stably at high temperatures and reducing the formation of tin oxide slag. The antimony and indium elements in wettability improver X are dissolved in the matrix in a specific ratio to form a solid solution, and the solid solution strengthening improves the hardness of the alloy and improves wettability. The addition of a small amount of silver can precipitate needle-like or granular Ag3Sn, which plays a role in dispersion reinforcement and reduces the brittleness of the tin-bismuth alloy.
[0004] In a first aspect, this application provides a tin-bismuth alloy material, which adopts the following technical solution: A tin-bismuth alloy material, by mass parts, comprises the following raw materials: 56-58 parts tin, 37-39 parts bismuth, 0.6-0.8 parts silver, 1.8-2.0 parts wettability improver X, 0.8-1.2 parts aluminum, 0.04-0.06 parts nano lanthanum oxide, 0.07-0.1 parts germanium, and 0.04-0.05 parts cerium, wherein the wettability improver X comprises antimony and indium.
[0005] By employing the above technical solutions, tin, as the main component, provides the basic properties of the alloy and improves its performance through synergistic effects with other elements. Bismuth improves the wettability of the alloy but is prone to coarsening and brittleness, requiring further improvement with other elements. Silver increases the alloy's strength through precipitation strengthening, reduces brittleness, and improves wettability. Wetness improver X (containing antimony and indium) improves the alloy's wettability and increases hardness through solid solution strengthening. Aluminum improves the alloy's strength, plasticity, and thermal fatigue strength, while also enhancing oxidation resistance. Nano-lanthanum oxide forms subgrain boundary structures at the alloy's grain boundaries, inhibiting internal oxidation and improving oxidation resistance. Germanium improves the alloy's oxidation resistance through surface segregation and stabilizes tin's performance at high temperatures. Cerium, together with germanium, alters the liquidus temperature of tin, reducing the formation of tin oxide slag. The synergistic effect of these elements in the alloy gives the tin-bismuth alloy excellent oxidation resistance, wettability, and mechanical properties.
[0006] Preferably, the mass ratio of antimony to indium is 4:1.
[0007] By adopting the above technical solution, firstly, indium and antimony are the main components of wettability improver X, which are dissolved in the matrix in a specific ratio to form a solid solution. This solid solution plays a role in solid solution strengthening in the alloy, increasing its hardness and improving its wettability. Furthermore, the synergistic effect of indium and antimony further optimizes the alloy's properties, resulting in better overall performance. The synergistic effect of indium and antimony may affect the alloy's microstructure and crystal structure, thus influencing its properties. Through reasonable design and selection of the alloy formulation, the interaction between indium and antimony can be maximized to achieve the best performance synergy and improve the wettability of the tin-bismuth alloy. In summary, the addition of indium and antimony to wettability improver X, interacting in a specific ratio, can play an important role in tin-bismuth alloy materials, improving alloy hardness and wettability through solid solution strengthening.
[0008] Preferably, the mass ratio of germanium to cerium is 2:1.
[0009] By adopting the above technical solution, germanium and cerium are added elements in a 2:1 mass ratio, maintaining a specific proportion in the alloy. Germanium exhibits surface segregation characteristics, precipitating on the alloy surface at high temperatures and preferentially combining with oxygen compared to elements like tin, thereby improving the surface oxidation resistance of the tin-bismuth alloy. The addition of germanium, in conjunction with cerium, alters the liquidus temperature of tin, ensuring its stable operation at high temperatures, reducing the formation of tin oxide slag, and further enhancing the alloy's oxidation resistance. The addition of cerium can modify the alloy's microstructure and properties, contributing to improved strength and heat resistance. When used in combination with germanium, cerium further enhances the surface segregation effect of germanium, strengthening its surface oxidation resistance. Therefore, at a 2:1 mass ratio, germanium and cerium work synergistically to improve the oxidation resistance of the tin-bismuth alloy, reduce oxidation behavior, and ensure normal operation of the alloy at high temperatures.
[0010] Secondly, this application provides a method for preparing a tin-bismuth alloy material, employing the following technical solution: As a general technical concept, this application also provides a method for preparing the above-mentioned tin-bismuth alloy material, including the following steps: S41, according to the mass fraction, tin is melted to 270-280°C, then wettability improver X, bismuth and silver are added, the temperature is raised to 300-320°C, germanium and cerium are added, the mixture is stirred continuously for 15-20 minutes, and then kept at the temperature and allowed to stand. S42. Add aluminum and nano-lanthanum oxide according to the mass fraction, continue heating to 350-360℃, sonicate for 8-12 min, and then maintain the temperature and stir thoroughly for 15-20 min to obtain a molten liquid. S43. The molten liquid is poured into a mold and cooled to obtain a tin-bismuth alloy material.
[0011] By adopting the above technical solution, in step S41, tin is first melted to 270-280℃, then wettability improver X, bismuth, and silver are added. The temperature is then raised to 300-320℃, and germanium and cerium are added. The mixture is stirred continuously for 15-20 minutes and then kept at this temperature. The key function of this step is to accurately add the various raw materials according to their mass proportions and gradually increase the temperature to ensure that the metals are fully fused and reacted, ensuring a uniform distribution of the alloy composition and improving the stability and consistency of the prepared alloy. In step S42, aluminum and nano-lanthanum oxide are added to the molten liquid, and the mixture is heated to 350-360℃. After ultrasonic treatment for 8-12 minutes, the temperature is maintained and the mixture is stirred thoroughly for 15-20 minutes to obtain the molten liquid. The purpose of this step is to generate high-temperature and high-pressure chemical micro-reactions through ultrasonic treatment, controlling heterogeneous nucleation, improving the grain refinement in the alloy, enhancing the crystal structure, and increasing the strength and toughness of the alloy. Simultaneously, it allows the nano-materials to be better dispersed uniformly, achieving optimal results. In step S43, the molten liquid is poured into a mold and cooled to obtain the tin-bismuth alloy material. This step involves cooling and solidifying the carefully prepared alloy melt to form a tin-bismuth alloy, ensuring the stability and consistency of the alloy microstructure and ultimately yielding an alloy material with excellent oxidation resistance, wettability, and mechanical properties. In summary, the preparation method in this application, through gradual temperature control of metal addition and ultrasonic treatment, makes the alloy preparation process more precise and efficient, fully utilizing the effects of various additive elements to ultimately obtain a high-performance tin-bismuth alloy material. This method helps improve the mechanical properties, oxidation resistance, and wettability of the alloy, and has significant engineering application value.
[0012] Preferably, after the molten liquid is poured into the mold, it is immersed in a heat treatment liquid at 148°C to cool it down to 148-152°C, then heated to 260-270°C, and then slowly cooled in a cooling liquid at 30°C to obtain a tin-bismuth alloy material.
[0013] By employing the above technical solution, immersion in a heat treatment solution at 148°C and stirring for 8-10 minutes is performed. This step aims to cool the high-temperature tin-bismuth alloy material to 148-152°C, which helps to refine the grains, resulting in a more uniform distribution and improving the alloy's hardness and strength. After heating to 260-270°C, slow cooling in a 30°C coolant helps to slow the cooling rate, avoiding internal stress caused by rapid cooling, while further improving the alloy's hardness. In summary, by adding heat treatment and slow cooling steps during the preparation process, the hardness, strength, and stability of the tin-bismuth alloy material can be further improved. These steps help optimize the alloy's microstructure and improve its properties, making them one of the key steps in improving the quality of tin-bismuth alloy materials.
[0014] Preferably, the heat treatment solution is a mixed solution of trimethylethylammonium chloride and sodium aluminum hydride, wherein the mass ratio of trimethylethylammonium chloride to sodium aluminum hydride is 12:1.
[0015] Preferably, the coolant is a mixed solution of mineral oil and isohexane, wherein the mass ratio of the mineral oil to the isohexane is 3:1-2.
[0016] In summary, the beneficial technical effects of this application are as follows: Firstly, by adding appropriate amounts of silver, wettability improver X, aluminum, nano-lanthanum oxide, germanium, and cerium, the coarsening and brittleness of bismuth can be slowed down, improving the mechanical and processing properties of the alloy. The addition of silver provides dispersion reinforcement, reducing the alloy's brittleness; antimony and indium in wettability improver X are dissolved in the matrix, enhancing the alloy's hardness and wettability; appropriate amounts of aluminum and nano-lanthanum oxide improve the alloy's strength and oxidation resistance.
[0017] Secondly, the mass ratio of germanium to cerium is 2:1. Through its surface segregation characteristics and liquid phase temperature regulation, the surface oxidation resistance of the alloy can be improved, the formation of oxide slag can be reduced, and the alloy can be used stably in high-temperature working environments.
[0018] In addition, the addition of nano-lanthanum oxide forms a subgrain boundary structure at the alloy grain boundary, which is conducive to the diffusion of aluminum atoms into the matrix and the formation of an oxide film, thereby improving the antioxidant performance.
[0019] Ultrasonic treatment can generate alternating low-pressure and high-pressure cycles in the molten metal, which helps control heterogeneous nucleation, enhance the crystal structure, refine the grains, and thus improve the strength and toughness of the alloy.
[0020] Heat treatment helps to refine the grains, resulting in smaller and more uniformly distributed solid particles, which improves the hardness and strength of the alloy. Detailed Implementation
[0021] The embodiments of this application will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of this application. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments used without specified manufacturers are all commercially available conventional products. The purity of the metal used is 99.95%; the purity of the nano-lanthanum oxide is 99.97%, and the average particle size is 30 nanometers.
[0022] Example 1 A tin-bismuth alloy material, by mass parts, comprises the following raw materials: 5.6 kg tin, 3.7 kg bismuth, 0.06 kg silver, 0.18 kg wettability improver X, 0.08 kg aluminum, 0.004 kg nano lanthanum oxide, 0.007 kg germanium, and 0.004 kg cerium, wherein the wettability improver X is composed of antimony and indium in a mass ratio of 4:1; A method for preparing a tin-bismuth alloy material includes the following steps: S41. According to the mass fraction, melt tin to 270°C, then add wettability improver X, bismuth and silver, heat to 300°C, add germanium and cerium, stir continuously for 20 minutes, and keep warm and stand. S42. Add aluminum and nano-lanthanum oxide according to the mass fraction, continue heating to 350℃, sonicate for 8 min, and then maintain the temperature and stir thoroughly for 15 min to obtain a molten liquid. S43. After pouring the molten liquid into the mold, it is immersed in a heat treatment liquid at 148°C to cool it down to 148°C, then heated to 260°C, and then slowly cooled in a cooling liquid at 30°C to obtain a tin-bismuth alloy material; the heat treatment liquid is composed of trimethylethylammonium chloride and sodium aluminum hydride in a mass ratio of 12:1; the cooling liquid is composed of mineral oil and isohexane in a mass ratio of 3:1.
[0023] Example 2 A tin-bismuth alloy material, by mass parts, comprises the following raw materials: 5.8 kg tin, 0.9 kg bismuth, 0.08 kg silver, 0.20 kg wettability improver X, 0.1 kg aluminum, 0.006 kg nano lanthanum oxide, 0.01 kg germanium, and 0.0045 kg cerium, wherein the wettability improver X is composed of antimony and indium in a mass ratio of 4:1; A method for preparing a tin-bismuth alloy material includes the following steps: S41. According to the mass fraction, melt tin to 280°C, then add wettability improver X, bismuth and silver, heat to 320°C, add germanium and cerium, stir continuously for 20 minutes, and keep warm and stand. S42. Add aluminum and nano-lanthanum oxide according to the mass fraction, continue heating to 360℃, sonicate for 12 min, and then maintain the temperature and stir thoroughly for 20 min to obtain a molten liquid; S43. After pouring the molten liquid into the mold, it is immersed in a heat treatment liquid at 148°C to cool it down to 152°C, then heated to 270°C, and then slowly cooled in a cooling liquid at 30°C to obtain a tin-bismuth alloy material; the heat treatment liquid is composed of trimethylethylammonium chloride and sodium aluminum hydride in a mass ratio of 12:1; the cooling liquid is composed of mineral oil and isohexane in a mass ratio of 3:2.
[0024] Example 3 A tin-bismuth alloy material, by mass parts, comprises the following raw materials: 5.7 kg tin, 3.8 kg bismuth, 0.07 kg silver, 0.19 kg wettability improver X, 0.09 kg aluminum, 0.005 kg nano lanthanum oxide, 0.008 kg germanium, and 0.005 kg cerium, wherein the wettability improver X is composed of antimony and indium in a mass ratio of 4:1; A method for preparing a tin-bismuth alloy material includes the following steps: S41. According to the mass fraction, melt tin to 275°C, then add wettability improver X, bismuth and silver, heat to 310°C, add germanium and cerium, stir continuously for 18 minutes, and keep warm and stand. S42. Add aluminum and nano-lanthanum oxide according to the mass fraction, continue heating to 355℃, sonicate for 10 min, and then maintain the temperature and stir thoroughly for 18 min to obtain a molten liquid. S43. After pouring the molten liquid into the mold, it is immersed in a heat treatment liquid at 148°C to cool it down to 150°C, then heated to 265°C, and then slowly cooled in a cooling liquid at 30°C to obtain a tin-bismuth alloy material; the heat treatment liquid is composed of trimethylethylammonium chloride and sodium aluminum hydride in a mass ratio of 12:1; the cooling liquid is composed of mineral oil and isohexane in a mass ratio of 3:1.5.
[0025] Example 4 Same as Example 3, except that germanium is 0.01 kg and cerium is 0.005 kg.
[0026] Comparative Example 1 Similar to Example 4, except that no aluminum and nano-lanthanum oxide were added to the raw materials.
[0027] Comparative Example 2 Similar to Example 4, except that germanium and cerium were not added to the raw materials.
[0028] Comparative Example 3 Similar to Example 4, except that no wetting improver X was added to the raw materials.
[0029] Comparative Example 4 Similar to Example 4, except that pure water is used as the heat treatment solution.
[0030] Performance testing Samples of the tin-bismuth alloy materials prepared in Examples 1-4 and Comparative Examples 1-4 were taken and made into tin-bismuth alloy welding rods for the following performance tests. Tensile strength test: Tested according to YST1580-2022 "Tension Test Method for Tin and Tin Alloys"; Elongation test: Tested according to GB / 11364-89 "Test method for spreadability and filler properties of brazing filler metal". The greater the elongation, the better the solderability of the tin-bismuth alloy welding electrode. Wettability: Wettability was determined using a MUSTSYSTEMLL solderability tester. The melting temperature was 230℃, each copper wire was 30mm long, the copper wire immersion speed was 10mm / s, the immersion depth was 3mm, the immersion time was 3s, and the mass was 30g. Antioxidant properties: The antioxidant properties were tested by static oxidation method. The temperature of the molten tin furnace was 270℃, the mass was 500g, the slag was scraped once every 60s, and the slag was taken once every 5min. Each group was tested 3 times, and the average value of the 3 tests was taken.
[0031] Table 1 Performance Tests Analyzing the data in Table 1, we can see that: 1) The tin-bismuth alloy materials prepared in Examples 1-4 have excellent oxidation resistance, wettability, mechanical properties and solderability. They have advantages such as slowing down coarsening and brittleness, improving alloy strength, improving the plasticity of tin-bismuth alloy, enhancing thermal fatigue strength and oxidation resistance.
[0032] 2) The performance comparison analysis of the tin-bismuth alloy materials prepared in Example 4 and Examples 1-3 shows that germanium and cerium can work synergistically at a mass ratio of 2:1 to improve the oxidation resistance of the tin-bismuth alloy, reduce oxidation behavior, and ensure normal use of the alloy in high-temperature environments.
[0033] 3) The performance comparison analysis of the tin-bismuth alloy materials obtained in Example 4 and Comparative Example 1 shows that using an appropriate amount of aluminum and nano-lanthanum oxide can improve the alloy strength, solder plasticity and oxidation resistance of the tin-bismuth alloy. Nano-lanthanum oxide is easy to form a subgrain boundary structure at the alloy grain boundary position, which is conducive to the diffusion of Al atoms to the matrix surface and the formation of Al2O3 oxide film upon contact with oxygen. Thus, during the alloy melting process, a continuous Al2O3 oxide film is formed on the alloy surface, which to a certain extent inhibits the oxidation behavior inside the alloy and greatly improves the oxidation resistance of the tin-bismuth alloy.
[0034] 4) A comparative analysis of the performance of the tin-bismuth alloy materials prepared in Example 4 and Comparative Example 2 shows that by using germanium and cerium as additive elements, germanium exhibits surface segregation characteristics, precipitating on the alloy surface at high temperatures. It preferentially combines with oxygen compared to elements such as tin, thereby improving the surface oxidation resistance of the tin-bismuth alloy. The addition of germanium, in conjunction with cerium, can alter the liquidus temperature of tin, ensuring its stable operation at high temperatures, reducing the formation of tin oxide slag, and further improving the alloy's oxidation resistance. At a mass ratio of 2:1, germanium and cerium work synergistically to improve the oxidation resistance of the tin-bismuth alloy, reduce oxidation behavior, and ensure normal use of the alloy in high-temperature environments.
[0035] 5) A comparative analysis of the performance of the tin-bismuth alloy materials prepared in Example 4 and Comparative Example 3 shows that indium and antimony are the main components of wettability improver X, which are dissolved in the matrix in a specific ratio to form a solid solution. This solid solution plays a role in solid solution strengthening in the alloy, increasing its hardness and improving its wettability. Furthermore, the synergistic effect of indium and antimony further optimizes the alloy's performance, resulting in better overall properties. Through reasonable design and selection of the alloy formulation, the interaction between indium and antimony can be maximized to achieve the best synergistic performance effect and improve the wettability of the tin-bismuth alloy.
[0036] 6) A comparative analysis of the performance of the tin-bismuth alloy materials prepared in Example 4 and Comparative Example 4 shows that the direct cooling treatment using a special heat treatment liquid in this application helps to refine the grains, resulting in a more uniform grain distribution and improved hardness and strength of the alloy. This also helps to optimize the microstructure of the alloy and improve its overall performance.
[0037] The above embodiments are only used to explain the technical solutions of this application and are not intended to limit it. Although the above embodiments have provided specific descriptions of this application, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of this invention. Any modifications and equivalent substitutions that do not depart from the spirit and scope of this application should be covered within the protection scope of this application.
Claims
1. A method for preparing a tin-bismuth alloy material, characterized in that, Includes the following steps: S41. According to the mass fraction, melt tin to 270-280℃, then add wettability improver X, bismuth and silver, heat to 300-320℃, add germanium and cerium, stir continuously for 15-20 minutes, and keep warm and stand. S42. Add aluminum and nano-lanthanum oxide according to the mass fraction, continue heating to 350-360℃, ultrasonically treat for 8-12 minutes, and then maintain the temperature and stir thoroughly for 15-20 minutes to obtain a molten liquid; S43. After casting the molten liquid into a mold, immerse it in a heat treatment liquid at 148℃ to cool it to 148-152℃, then heat it to 260-270℃, and then slowly cool it in a cooling liquid at 30℃ to obtain a tin-bismuth alloy material; The heat treatment solution is a mixed solution of trimethylethylammonium chloride and sodium aluminum hydride; The mass ratio of trimethylethylammonium chloride to sodium aluminum hydride is 12:1; The coolant is a mixed solution of mineral oil and isohexane; The mass ratio of the mineral oil to the isohexane is 3:1-2; The amounts of each raw material, measured by mass, are as follows: The composition comprises 56-58 parts tin, 37-39 parts bismuth, 0.6-0.8 parts silver, 1.8-2.0 parts wettability improver X, 0.8-1.2 parts aluminum, 0.04-0.06 parts nano lanthanum oxide, 0.07-0.1 parts germanium, and 0.04-0.05 parts cerium, wherein the wettability improver X is antimony and indium; The mass ratio of antimony to indium is 4:1; The mass ratio of germanium to cerium is 2:1.
Citation Information
Patent Citations
Lead-free alloy solder for photovoltaic welding strips and preparation method thereof
CN108393608A
High-heat-resistance lead-free tin bar and preparation method thereof
CN116140863A
Soldering tin material for chip packaging and preparation method thereof
CN116460481A
